Retrospective analysis of spring barley cultivars developed by Omsk breeders (1936–2021) - P. N. Nikolaev; O. A. Yusova; N. I. Aniskov; O. N. Kovaleva; I. V. Safonova (Труды по прикладной ботанике, генетике и селекции, 2023)
Plant breeding is an endless conveyor belt: cultivars developed earlier are included in hybridization plans and become the sources for new ones. The main tasks in barley improvement through breeding include raising the productivity of cultivars, improving their quality, and strengthening disease resistance. Correct selection, use, and studying of the source material – that is the key to successful breeding efforts. The first and most important step in constructing a cultivar is the process of hybridization. A valuable source of aid, and often the basis for newly developed cultivars, is the global collection of VIR, whose importance can hardly be overestimated. From 1936 to 2021, 27 barley cultivars were released: they are widely cultivated in Russia and Kazakhstan. Of these, 19 cultivars were obtained by pair hybridization; 4 cultivars by the complex stepwise hybridization technique; 4 cultivars through individual selection using the population approach. Despite the high importance of germplasm collection materials, 21 cultivars were produced by hybridization using a genotype selected at Omsk as one of the parental forms: in 16 cultivars, a local genotype was used as a maternal parent; in 12, as a paternal one; and in 8 cultivars, both parent forms were bred at Omsk Agricultural Scientific Center. Our retrospective analysis of a number of Omsk spring barley cultivars, on the one hand, confirms the earlier conclusions of Siberian scientists about a limited number of base crop cultivars, and on the other, attests to very rich pedigrees of spring barley cultivars in terms of the number of parent forms from the VIR global collection. Siberian barley ecotypes, characterized by increased adaptability to local harsh climate factors, should be further preserved in the national crop germplasm repository at VIR.